2018
DOI: 10.1093/biolre/ioy054
|View full text |Cite
|
Sign up to set email alerts
|

Histone 3 lysine 4, 9, and 27 demethylases expression profile in fertilized and cloned bovine and porcine embryos†

Abstract: Epigenetic modifications in the C-terminal domain of histones coordinate important events during early development including embryo genome activation (EGA) and cell differentiation. In this study, the mRNA expression profile of the main lysine demethylases (KDMs) acting on the lysine 4 (H3K4), 9 (H3K9), and 27 (H3K27) of the histone H3 was determined at pre-, during and post-EGA stages of bovine and porcine embryos produced by in vitro fertilization (IVF) and somatic cell nuclear transfer (SCNT). In IVF embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 61 publications
1
30
0
3
Order By: Relevance
“…This includes a number of different KDMs, the enzymes responsible for demethylating lysine residues in histones, whose expression pattern was shown to dramatically change in early developing embryos of different species (Dahl et al, 2016;Zhang et al, 2016;Hormanseder et al, 2017;Glanzner et al, 2018). In this study, we chose to investigate the role of KDM5B and KDM5C, both known to act on H3K4me, during porcine embryo development because our previous studies revealed that their expression increased markedly, but transiently around the OET stage in porcine embryos (Glanzner et al, 2018), and because KDM5B attenuation was shown to reduce development of porcine embryos (Huang et al, 2015). First, we found that attenuation of KDM5B or KDM5C similarly decreased embryo development rates, but attenuation of both had no synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes a number of different KDMs, the enzymes responsible for demethylating lysine residues in histones, whose expression pattern was shown to dramatically change in early developing embryos of different species (Dahl et al, 2016;Zhang et al, 2016;Hormanseder et al, 2017;Glanzner et al, 2018). In this study, we chose to investigate the role of KDM5B and KDM5C, both known to act on H3K4me, during porcine embryo development because our previous studies revealed that their expression increased markedly, but transiently around the OET stage in porcine embryos (Glanzner et al, 2018), and because KDM5B attenuation was shown to reduce development of porcine embryos (Huang et al, 2015). First, we found that attenuation of KDM5B or KDM5C similarly decreased embryo development rates, but attenuation of both had no synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the signaling pathways affected by KDM5B attenuation during embryo development were not characterized. In a previous study, we demonstrated that the relative mRNA expression of KDM5B and KDM5C (also known as JARID1C, and another KDM of H3K4), was dramatically increased during OET in porcine and bovine embryos (Glanzner et al, 2018), which suggested they are both involved in OET regulation in these species.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Aberrant H3K9 and H3K27 methylation levels were observed in pig SCNT embryos (Cao et al 2015, Huang et al 2016, Xie et al 2016. The histone lysine demethylases which control the methylation status of lysine residues in the histone H3 (H3K4, H3K9, H3K27) were also observed to be improperly expressed during cell reprogramming in porcine and bovine SCNT embryos compared with that of in vitro fertilized (IVF) embryos, proposing an improper establishment of the histone methylation in SCNT embryos (Glanzner et al 2018). Therefore, the histone methylation marks required modulation to sustain normal development in SCNT embryos.…”
Section: Introductionmentioning
confidence: 99%
“…in donor cells or in early embryos). We then hypothesized that distinct time of expression between H3K9me2 writers and erasers might explain the lower levels of H3K9me2 since the expression of EHMT1 and EHMT2 in bovine is higher in oocytes than in early embryos 29 while the expression of lysine demethylases is increased later in development 30 . Herein, we found no effect of the UNC0678 treatment when main regulatory genes were analyzed (Figure 7).…”
Section: Discussionmentioning
confidence: 99%